THE ROLE OF HIGH-RESOLUTION CT IN THE DETECTION AND DIFFERENTIATION OF PULMONARY CHANGES BETWEEN UIP AND NSIP PNEUMONIA - Dimitrijevikj, Kristina; Mitreska, Nadica; Prgova-Veljanova, Biljana; Nikolova, Sonja; Pashoska, Milkica (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
High-resolution computed tomography (HRCT) has a central role in the diagnosis of interstitial lung diseases, particularly in differentiation between UIP and NSIP pattern. To analyze the distribution and characteristic radiological findings of interstitial lung changes with HRCT in UIP and NSIP pattern and to show the efficacy of this method in distinguishing these two entities.    High-resolution computed tomography was performed on a 128-slice PHILIPS INCISIVE CT scanner, using 1 mm slices and a special reconstruction algorithm. A total of 37 patients at the University Clinic for Pulmonology and Allergology-Skopje were examined with UIP and NSIP pattern.  Of the total number of patients, 23 showed a UIP pattern on HRCT, 15 of them were men, and 8 were women with a predominant age over 60 years and most were smokers. Out of 14 patients with NSIP pattern, 11 are women and 3 are men. Half of them are under the age of 60, where the smoking status is significantly lower compared to UIP patients.    This article demonstrates HRCT finding and its distribution in UIP pattern associated with idiopathic pulmonary fibrosis and NSIP pattern commonly present in connective tissue diseases. These two entities clearly differ in their specific radiological signs, which is very significant in the therapy and prognosis of  interstitial lung diseases. Key words:   UIP pattern, NSIP pattern, HRCT, interstitial lung diseases